STRATEGI PEMECAHAN MASALAH DAN PENGAMBILAN KEPUTUSAN PADA ORGANISASI MAHASISWA PKPMI ACEH - Muhammad Ashmal; Fakhri; Raihan (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
Student organizations serve as crucial platforms for shaping students’ character, leadership, and social skills. However, despite their strategic roles, these organizations often face internal challenges such as interpersonal conflicts, differing opinions, and weak coordination. If left unaddressed, these issues can hinder the implementation of work programs and diminish members' enthusiasm for organizational involvement. Such challenges also threaten the sustainability and effectiveness of the organization itself. This study explores how conflict resolution processes are carried out within the Indonesian National Association of Students and Scholars in Aceh (PKPMI Aceh), and ideantifies both the supporting and inhibiting factors involved. Adopting a qualitative case study approach, data were collected through observations, in-depth interviews with five key informants, and organizational documentation. The findings reveal that problem-solving is primarily achieved through deliberation and consensus, emphasizing open communication and inclusive participation. Supporting factors include a strong sense of solidarity, participatory leadership, and an inclusive organizational culture. Conversely, the main obstacles involve lack of discipline, sectoral ego, and limited organizational experience. In conclusion, the effectiveness of conflict resolution in student organizations is strongly influenced by internal communication and collective commitment to resolving disputes with wisdom.